2019
DOI: 10.1111/jdv.15859
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and roles of extracellular vesicles released by epidermal keratinocytes

Abstract: Keratinocytes, which constitute 90% of the cells in the epidermis of the skin, have been demonstrated to communicate with other skin cells such as fibroblasts, melanocytes and immune cells through extracellular vesicles (EVs). This communication is facilitated by the enriched EV biomolecular cargo which regulates multiple biological processes within skin tissue, including cell proliferation, cell migration, anti‐apoptosis, pigmentation transfer and extracellular matrix remodelling. This review will provide an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 72 publications
0
16
0
Order By: Relevance
“…Keratinocyte EV secretion is induced by various stimuli, such as hypoxia, irradiation, and starvation. Increasing evidence depicts that keratinocyte-derived EVs play a role in the wound healing process [ 79 , 80 ]. Keratinocyte-derived exosomes can affect the dendritic cell phenotype and cytokine production [ 81 ].…”
Section: Crosstalk Between Keratinocytes and Immune Cells During Smentioning
confidence: 99%
“…Keratinocyte EV secretion is induced by various stimuli, such as hypoxia, irradiation, and starvation. Increasing evidence depicts that keratinocyte-derived EVs play a role in the wound healing process [ 79 , 80 ]. Keratinocyte-derived exosomes can affect the dendritic cell phenotype and cytokine production [ 81 ].…”
Section: Crosstalk Between Keratinocytes and Immune Cells During Smentioning
confidence: 99%
“…EVs have been shown to transfer information between cells [29]. Our proteomic analysis findings show that EV-derived proteins strongly associated with the MAP-Kinase pathway (Fig.…”
Section: The Mapkinase Pathway Is Activated By Evsmentioning
confidence: 66%
“… 5 , 11 For instance, keratinocytes which make up 90% of the cells in the epidermis, can communicate with other skin cells such as fibroblasts, melanocytes and immune cells through EVs. 12 , 13 It was also reported that keratinocyte-EVs can stimulate the expression of metalloproteinase-1 (MMP1) in dermal fibroblasts to modify the ECM. 12 In addition, keratinocyte-EVs and human immortalized keratinocyte (HaCaT)-EVs stimulate fibroblasts migration and induce fibroblast-mediated endothelial tube formation by activating the ERK1/2, JNK, Smad, and p38 signaling pathways, hence mediating wound healing.…”
Section: Skin and Skin Derived Extracellular Vesiclesmentioning
confidence: 99%
“… 12 , 13 It was also reported that keratinocyte-EVs can stimulate the expression of metalloproteinase-1 (MMP1) in dermal fibroblasts to modify the ECM. 12 In addition, keratinocyte-EVs and human immortalized keratinocyte (HaCaT)-EVs stimulate fibroblasts migration and induce fibroblast-mediated endothelial tube formation by activating the ERK1/2, JNK, Smad, and p38 signaling pathways, hence mediating wound healing. 14 Moreover, keratinocyte-EVs can affect other keratinocytes, macrophages, dendritic cells and neutrophils during skin inflammation.…”
Section: Skin and Skin Derived Extracellular Vesiclesmentioning
confidence: 99%